Successful university-school partnerships: An interpretive framework to inform partnership practice. (November 2016) - Jones, Mellita; Hobbs, Linda; Kenny, John; Campbell, Coral; Chittleborough, Gail; Gilbert, Andrew; Herbert, Sandra; Redman, Christine
Abstract: This paper presents an Interpretive Framework stemming from a longitudinal and iterative multiple case study of five Australian universities examining the cogent and unique practices underpinning their established and successful school-based science teacher education programs. Results from interviews with teacher educators, school staff and pre-service teachers, show four components that guide the successful and sustainable use of university-school partnerships. These components: Guiding Pedagogical Principles; Growing University-School Partnerships; Representations of Partnership; and Growth Model provide a scaffold for initiating, growing and sustaining partnerships that maximise the benefits for all. The essential role of both university and school staff is also highlighted. Highlights: Four-part Interpretive Framework to guide university-school partnership activity. Growing University-School Partnerships: Guide to initiate, implement and evaluate partnership activity. Representations of Partnership: Connective, Generative and Transformative typology. Partnership typology represents levels of embeddedness rather than a hierarchy. Growth Model: Enablers, locus and evidence of pre-service teacher's growth.